Three-week Nutritional Supplementation Effect on Long-term Nutritional Status of Patients With Mild Alzheimer Disease - Odete Luisa V Vicente de Sousa (2012)
Short-term nutritional supplements enable an improvement in Alzheimer patients' nutritional status, but it remains to be seen whether they will be sufficient to improve long-term nutritional status. The aim of this study was to evaluate the long-term impact of a 3-week nutritional supplementation on the nutritional status of undernourished patients with probable mild Alzheimer disease. A 21-day prospective randomized nonblinded controlled trial was conducted. Patients were followed-up for an additional period until the 90th day after the beginning of the intervention. Intervention resulted in significant improvements in Mini Nutritional Assessment (MNA) score [Mean = 1.4, standard deviation (SD) = 0.8 vs. 0.0 (0.1) in the control group, P < 0.001] and also in anthropometrical and serum biomarkers of Alzheimer disease (AD) patients' nutritional status. Further improvements in the AD patients' MNA mean score = 1.4 (SD = 2.3) versus -0.5 (SD - 0.6) in the control group (P - 0.003) were seen at 90 days follow-up. Data show that a 3-week nutritional supplementation has a positive long-term impact on the nutritional status of undernourished patients with mild probable AD.